PENGARUH INVESTASI TERHADAP PERTUMBUHAN EKONOMI KOTA SURABAYA DAN PEMILIHAN LOKASI PERMUKIMAN DAN TRANSPORTASI DI KOTA SURABAYA - JAMHADI, * (Program Doktor Ilmu Ekonomi, 2009)
The objective of this Dissertation (1) to verify and analyze the influence of private investment toward economical development. (2) to ensure and analyze the influence of government investment toward the economical development. The find in this dessertatition are (1) Government investment and private investment fromSurabayaand its hinterland city influences enough for economical growth. (2) the existing of hinterland area which influences the economical growth are Pasuruan and Mojokerto. Practical implication for Surabaya Local Government are: (1) to stimulate the village economic growth through the improvement of secondary town plan in the form of small business which give service and marketing of farming tools and material in order to stimulate of the absorption of employee more over in agriculture sector (2) the improvement of administration capacity for secondary town to organize the manufacture growing more efficient and regional development. Keywords: Migrant; Economic Growth; Urban Economy; Central Business District (CBD).